OTTOMAN CONSULATE GENERAL IN BATAVIA: ESTABLISHMENT, CONSUL GENERAL ALİ GALİB BEY AND HIS REPORT - Diren ÇAKILCI (International Journal of Eurasia Social Sciences, 2017)
The political, religious and economic relations of the Ottoman State over the Indian Ocean have existed since long ago, even if limited. Especially during the Tanzimat period, the activities of the consulates and the appointed consul in these regions have increased the interest of the Ottoman State to the geography mentioned. The information gathered about the Muslims of South Asia in the frame of Sultan II Abdulhamid’s Pan-Islamic policy contributed to the shaping of Caliphate politics. In this context, the activities of the consulates such as Bombay, Calcutta, Batavia also shaped to the religious, political and economic policies of the Ottoman State while the South Asian Muslims developed the loyalty and sympathy to the Caliph. In this sense, the report of presented to Sultan II Abdulhamid is of great importance. This report, prepared by Ali Galib Bey, who wandered the majority of the islands on the Indian Ocean through the post of Batavia consulate, was written after Ali Galib’s appointment to Bombay. Ali Galib points out the importance of the relationship between Muslims and the Caliph. In this study, the establishment and activities of the Batavia and Bombay consulates will be mentioned, and then sought to illlimunate on the socio-economic structure and commercial relations of the Indian Ocean islands through the persperctive of Ottoman Consul Ali Galib Bey. As a result, this study will contribute to the researches of the commercial and political activities of Ottoman State on Indian Ocean.